S100A4 is frequently overexpressed in lung cancer cells and promotes cell growth and cell motility - Chen, Na; Sato, Daisuke; Saiki, Yuriko; Sunamura, Makoto; Fukushige, Shinichi; Horii, Akira (Biochemical and biophysical research communications, 2014)
•We observed frequent overexpression of S100A4 in lung cancer cell lines.•Knockdown of S100A4 suppressed proliferation in lung cancer cells.•Forced expression of S100A4 accelerated cell motility in lung cancer cells.•PRDM2 was found to be one of the downstream suppressed genes of S100A4. S100A4, a small calcium-binding protein belonging to the S100 protein family, is commonly overexpressed in a variety of tumor types and is widely accepted to associate with metastasis by regulating the motility and invasiveness of cancer cells. However, its biological role in lung carcinogenesis is largely unknown. In this study, we found that S100A4 was frequently overexpressed in lung cancer cells, irrespective of histological subtype. Then we performed knockdown and forced expression of S100A4 in lung cancer cell lines and found that specific knockdown of S100A4 effectively suppressed cell proliferation only in lung cancer cells with S100A4-overexpression; forced expression of S100A4 accelerated cell motility only in S100A4 low-expressing lung cancer cells. PRDM2 and VASH1, identified as novel upregulated genes by microarray after specific knockdown of S100A4 in pancreatic cancer, were also analyzed, and we found that PRDM2 was significantly upregulated after S100A4-knockdown in one of two analyzed S100A4-overexpressing lung cancer cells. Our present results suggest that S100A4 plays an important role in lung carcinogenesis by means of cell proliferation and motility by a pathway similar to that in pancreatic cancer.